Nederlandse nasionalisme en Afrikanernasionalisme - ’n vergelyking - Klerk, P. de (Koers, 1996)
A comparison between Dutch and Afrikaner nationalism The development of Dutch nationalism during the nineteenth century was strongly influenced hy events in South Africa and reached its zenith during the Anglo-Boer War of 1899-1902. The beginnings of Afrikaner nationalism are to he found in the late nineteenth and early twentieth centuries and were to a certain extent stimulated by Dutch nationalism. This article compares some features of both nationalisms, aiming especially to find similarities which might have been caused by the influence of one of these manifestations of nationalism on the other. It is concluded, however, that the similarities between these manifestations of nationalism are mainly caused by the characteristics of nationalism as a genera! phenomenon. In this article the role of Calvinist religion and philosophy in the development of Dutch and Afrikaner nationalism is briefly examined. It seems as if in both the Netherlands and South Africa influential Calvinist intellectuals with strong nationalist views p layed a role, but that they d id not have a major impact on the development of nationalism in either of the two countries. Both Dutch and the Afrikaner nationalists, however, regarded the Calvinist worldview and lifestyle of their forebears as essential features of Dutch and Afrikaner national identities.